If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y=1/2*0-2
We move all terms to the left:
y-(1/2*0-2)=0
We get rid of parentheses
y+2-1/2*0=0
We multiply all the terms by the denominator
y*2*0-1+2*2*0=0
We add all the numbers together, and all the variables
y*2*0-1=0
Wy multiply elements
0-1=0
We add all the numbers together, and all the variables
-1!=0
There is no solution for this equation
| 4x=6x-38 | | 4^x=46 | | X-4/3+2x-3/35=5x-32/9-x+9/28 | | 52-13q=0 | | 3x/2+12=20 | | 42x=-11x-212 | | 3x/2+8=20 | | m+m+46=90 | | 90=m(m+46) | | 5-3x/2=2 | | 12x-3x-5x=0 | | 10p+8=12p-5 | | 3.9t-9.6t=-25.3 | | y/5=-18 | | 5(2x-8)+15=-15. | | 2/3*t=8/9 | | 3*(-5x+3)=-14*(x+1) | | -2x+5+6x+1=-2x+6x+10 | | 7x-3-6x=5+22 | | 7x-3-6x=24+3 | | 4z/7-9=7 | | (-3x)-4=2x-14 | | x/9-8=0 | | 3(x+2)2=15 | | x=3x+5-(2x-9) | | 3(x-5)+7=0 | | -x+13=-27 | | 2x–7=3x+2 | | 5n-9=43 | | 16(7)=14x(8x) | | x-10+4x-25+x-5=180 | | 8x+2=6x-1+7x+7 |